Winters without women: social change, split households and gendered labour in rural Mongolia. Issue 3 (4th March 2018) - Ahearn, Ariell
Abstract: In this article, I use absence as a lens to explore social change and masculinity in rural Mongolia, with a focus on household splitting during winter months. Since the breakdown in state-sponsored dormitory systems, many mobile pastoralists split their households to accommodate children during the school year. This results in women moving to settled centres while men remain in pastures to care for livestock. In critical reflections on rural work, both male and female herders have underscored concerns around the absence of women in rural homes. In Mongolia, absence has different implications for men and women, gendered division of labour and social roles, which are tied to household economies and pastoralist work practices. Drawing from ethnographic field research, the cases contribute to understandings of the co-constitutive nature of space and society, and attempts to dislodge ideas about the fixed nature of households in rural Mongolia.